Optimal support for elite sprinters using a minimal, adequate, and accurate approach - Washif, J. A.; Pyne, D. B. (International Journal of Sports Physiology and Performance, 2025)
Background In high-performance sport, the support provided by sport scientists and other staff can be a valuable resource for coaches and athletes.